Auditory cortical plasticity after cochlear implantation in asymmetric hearing loss is related to spatial hearing: a PET H215O study. (28th May 2022) - Karoui, Chadlia; Strelnikov, Kuzma; Payoux, Pierre; Salabert, Anne-Sophie; James, Chris J; Deguine, Olivier; Barone, Pascal; Marx, Mathieu
Abstract: In asymmetric hearing loss (AHL), the normal pattern of contralateral hemispheric dominance for monaural stimulation is modified, with a shift towards the hemisphere ipsilateral to the better ear. The extent of this shift has been shown to relate to sound localization deficits. In this study, we examined whether cochlear implantation to treat postlingual AHL can restore the normal functional pattern of auditory cortical activity and whether this relates to improved sound localization. The auditory cortical activity was found to be lower in the AHL cochlear implanted (AHL-CI) participants. A cortical asymmetry index was calculated and showed that a normal contralateral dominance was restored in the AHL-CI patients for the nonimplanted ear, but not for the ear with the cochlear implant. It was found that the contralateral dominance for the nonimplanted ear strongly correlated with sound localization performance (rho = 0.8, P < 0.05). We conclude that the reorganization of binaural mechanisms in AHL-CI subjects reverses the abnormal lateralization pattern induced by the deafness, and that this leads to improved spatial hearing. Our results suggest that cochlear implantation enables the reconstruction of the cortical mechanisms of spatial selectivity needed for sound localization.